Upaya Mengembangkan Kemampuan Sikap Sosial Anak Melalui Metode Sosiodrama Pada Anak Kelompok B Di TK Pertiwi Gunung Simo Boyolali - Saputra, Dian Exo, Drs. M. Djaelani, M. Pd (2016)
The purpose of this study was to determine the development of methods sociodramas in improving social attitudes in children in group B at Tk Pertiwi Mount Simo Boyolali. This research is a class action (PTK) using descriptive data analysis and quantitative, that is by analyzing data from the child's development stage and Pre cycle plus the first cycle to the third cycle. objects used this study is children in group B consisting of 21 children. and research data collection techniques using methods of observation and documentation methods. so that the results showed a result in social attitudes in children using sociodramas. at this stage of the first cycle, the researchers obtained a percentage of 19%, whereas the percentage has not been completed by 81%. 20% consisted of 4 children who have mastery with an average value of 2.3. after researchers conducted the second cycle of the obtained results in the social attitudes of children using methods sociodramas much as 47.6% or 11 children who suffered the thoroughness and 10 children who have shown that children do not meet the completeness, with the average value reached 2.9. and the third cycle in developing social attitudes of children with sociodramas method can be increased also by 90.5% or completeness results of 19 children, and 9.5% or 2 children who otherwise do not meet the completeness criteria. the third cycle the average value of completeness reached 3.6. depat researchers thus conclude that the cycle I, II, III in an effort to develop a child's social attitudes by using methods sociodramas on children in group B Tk Pertiwi Mount Simo Boyolali in the academic year 2013/2014